2021
DOI: 10.3390/nano11030794
|View full text |Cite
|
Sign up to set email alerts
|

Electronics of Anion Hot Injection-Synthesized Te-Functionalized Kesterite Nanomaterial

Abstract: Metal chalcogenides such as copper zinc tin sulfide (CZTS) have been intensively studied as potential photovoltaic cell materials, but their viability have been marred by crystal defects and low open circuit potential (Voc) deficit, which affected their energy conversion efficiency. Strategies to improve on the properties of this material such as alloying with other elements have been explored and have yielded promising results. Here, we report the synthesis of CZTS and the partial substitution of S with Te vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…Raman spectra of S‐alloyed CZT(Te–S) nanoparticles, presented in Figure 8 , reveal the appearance of an additional strong line around 328–330 cm −1 , very similar to what was reported in Ref. [23]. The position of this new line is very close to the one in pure CZTS, where it corresponds to one of the A‐modes.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Raman spectra of S‐alloyed CZT(Te–S) nanoparticles, presented in Figure 8 , reveal the appearance of an additional strong line around 328–330 cm −1 , very similar to what was reported in Ref. [23]. The position of this new line is very close to the one in pure CZTS, where it corresponds to one of the A‐modes.…”
Section: Resultssupporting
confidence: 84%
“…The calculated bandgap magnitude was found to be 0.45 eV, a value smaller in comparison with experimental findings of 0.8–0.9 eV. [ 11–13,23 ] Taking into account the well‐known shortcoming of DFT in the determination of the bandgap value for semiconductors [ 24 ] and to facilitate a comparison of the electronic and optical properties with experiment, we performed a “scissor shift” of all valence band states by 0.4 eV, so that the calculated bandgap at the Brillouin zone center (Figure 1) matches the experimental value.…”
Section: Resultsmentioning
confidence: 98%
“…As illustrated in Figure 2a , peak I intensities were higher in the XRD pattern of the A‐DDC group, suggesting that aloin may induce a shorter lateral spacing between collagen molecules (Green et al., 2017 ). This conjecture is further supported by the observed increase in 2 θ angles of the diffraction peak I and III in the A‐DDC group, indicating that the addition of aloin reduces the spacing between collagen molecules (Ding et al., 2019 ; Nwambaekwe et al., 2021 ). Peak II, which can be seen at roughly 2 θ ~20°, is due to the diffusive scattering caused by the presence of random‐coil structures embedded within the collagen fibers (Giraud‐Guille et al., 2000 ).…”
Section: Discussionmentioning
confidence: 76%
“…In the case of the modified electrode, the data obtained revealed that the electrodes underwent three reactions that are capacitive. 24,[83][84][85] The circuit consisted of R s and two R ct 's which have been defined. R s and R ct of 133 Ω and 894 Ω, respectively, were obtained for bare SPCE.…”
Section: Electrochemical Analysesmentioning
confidence: 99%